2012
DOI: 10.3109/13693786.2012.677862
|View full text |Cite
|
Sign up to set email alerts
|

Protothecosis: report of a case with 20-year follow-up, and review of previously published cases

Abstract: We present a Prototheca wickerhamii wound infection case that failed treatment with ketoconazole but was cured with amphotericin-B plus tetracycline. The patient was immunocompetent but had had local steroid injections. We reviewed another 159 cases from the literature. Prototheca has infected many areas of the human body, but most often skin, olecranon bursa, or wounds. Prior treatment with steroids and immune deficiencies are contributing factors. Itraconazole and fluconazole are reasonable initial treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
110
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(122 citation statements)
references
References 126 publications
0
110
0
5
Order By: Relevance
“…Currently, it is generally accepted that six species belong to the genus Prototheca ; namely, P. wickerhamii , P. zopfii , P. blaschkeae , P. cutis , P. ulmea and P. stagnora [3-5] of which the first four species have been shown to cause infection in animals, such as cattle and dogs [6-9], and humans [2,10,11]. Recently, an increasing number of human cases of Prototheca infection have been reported, including opportunistic infection in immune compromised individuals [2,11]. Therefore, diagnosis of protothecosis and identification of the causative Prototheca species are becoming more and more important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is generally accepted that six species belong to the genus Prototheca ; namely, P. wickerhamii , P. zopfii , P. blaschkeae , P. cutis , P. ulmea and P. stagnora [3-5] of which the first four species have been shown to cause infection in animals, such as cattle and dogs [6-9], and humans [2,10,11]. Recently, an increasing number of human cases of Prototheca infection have been reported, including opportunistic infection in immune compromised individuals [2,11]. Therefore, diagnosis of protothecosis and identification of the causative Prototheca species are becoming more and more important.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that there have been cases in which the identification was not definitive, although P. wickerhamii among the pathogenic Prototheca spp. appears to be the most common cause for human infection [2,11]. Recently, it has been shown that molecular techniques, such as polymerase chain reaction (PCR) genotyping using species- and genotype-specific primers, nucleotide sequencing of ribosomal DNA (rDNA), proteomic analysis, and real-time PCR could be useful for identification of Prototheca spp.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, six species are included in the genus Prototheca: Prototheca wickerhamii, Prototheca zopfii, Prototheca blaschkeae, Prototheca cutis, Prototheca ulmea and Prototheca stagnora (Roesler et al, 2006;Satoh et al, 2010;Roesler, 2011). The first four species have been shown to cause infections in animals, such as cattle and dogs (Frank et al, 1969;Hollingsworth, 2000;Jánosi et al, 2001;Stenner et al, 2007), and humans (Matsuda & Matsumoto, 1992;Lass-Flörl & Mayr, 2007;Todd et al, 2012). Recently, an increasing number of human cases of protothecosis have been reported, including opportunistic infection in immune-compromised individuals (Todd et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The first four species have been shown to cause infections in animals, such as cattle and dogs (Frank et al, 1969;Hollingsworth, 2000;Jánosi et al, 2001;Stenner et al, 2007), and humans (Matsuda & Matsumoto, 1992;Lass-Flörl & Mayr, 2007;Todd et al, 2012). Recently, an increasing number of human cases of protothecosis have been reported, including opportunistic infection in immune-compromised individuals (Todd et al, 2012). Clinical diagnoses of protothecosis had traditionally been made by histopathological examination of affected tissues and morphological and biochemical examinations of the isolated organism (Matsuda & Matsumoto, 1992;Lass-Flörl and Mayr, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, in China, the real number of Protothecosis cases may be more than that reported in the literature according to the environmental conditions and population. The number of protothecosis cases reported has reached 160 cases up to June, 2011 in the world, showing an increasing trend [9]. Human protothecosis have been classified into three clinical forms: (1) cutaneous and /or subcutaneous infections.…”
Section: Discussionmentioning
confidence: 99%